Preparation method and application of potassium humate grafted polycondensate Graft HA-K Polymer
Potassium humate is prepared by hydrothermal alkali extraction and synthesized potassium humate graft polycondenser Graft HA-K Polymer, which solves the problem of failure of traditional drilling fluid viscosity reducers in high temperature environments, and achieves efficient reduction of drilling fluid viscosity and resistance Salt capacity reduces environmental pollution and costs and provides cost-effective drilling additives.
Patent Information
- Application Number
- CN202411010400.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2024-12-17
AI Technical Summary
The traditional humic acid drilling fluid viscosity reducer fails in high temperature environments, resulting in increased viscosity of the drilling fluid, difficulty in starting the pump, and problems of environmental pollution and high cost during extraction and utilization.
Potassium humate is prepared by hydrothermal alkali extraction, and the potassium humate graft polycondenser is synthesized with Na-HPAN, urea, formaldehyde, and AAM. It has high temperature resistance and salt resistance, and is used in drilling fluids. anti-salt and viscosity-reducing agent.
The effective viscosity reduction rate at 177.39℃ high temperature and 8000mg·L-1 high salt point was achieved at 63.16%. The yield was improved by modifying the catalyst, environmental pollution was reduced, and cost-effective drilling additives were provided.
Smart Images

Figure CN119143946A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of resource utilization of biomass solid waste, and specifically relates to a preparation method of a potassium humate graft polycondensate Graft HA-K Polymer and application of the Graft HA-K Polymer in a drilling fluid salt resist and viscosity reducer. Background Art
[0002] Organic water-soluble fertilizers are water-soluble fertilizers made from natural organic matter through chemical or biotechnology treatment. They usually contain various nutrients required for crop growth, such as nitrogen, phosphorus, potassium, etc., and have the value of providing nutrients and increasing soil fertility. However, organic water-soluble fertilizers generally have problems such as high production costs, fast nutrient release, and lack of trace elements in agricultural production, which may lead to a lack of trace elements in the soil and affect the growth and yield of crops. Artificially prepared humic acid water-soluble fertilizers can provide comprehensive nutrition, improve soil structure, and regulate soil pH. It is an important supplement to organic fertilizers and is of great significance for promoting sustainable agricultural development and improving crop yield quality.
[0003] Drilling fluid is the blood of drilling. The rheological properties of drilling fluid are very important for carrying cuttings, maintaining the stability of the well wall, and ensuring safe drilling. However, with the increasing number of deep and ultra-deep wells and the increasingly complex geological conditions, higher requirements are placed on drilling fluid under high temperature, high pressure and high mineralization conditions. When drilling through high-pressure salt water layers and high-temperature formations, the drilling fluid must control appropriate rheology. During the use of drilling fluid, the network structure formed by the drilling fluid is often enhanced due to temperature increase, salt invasion or calcium invasion, or treatment agent failure, and the viscosity and shear force of the drilling fluid increase. If the viscosity and shear force are too large, it will cause problems such as difficulty in starting the pump and difficulty in removing the cuttings. Therefore, during the use and maintenance of drilling fluid, it is often necessary to add viscosity reducers to reduce the viscosity and shear force of the drilling fluid so that it has suitable rheology.
[0004] At present, the commonly used viscosity reducers can be mainly divided into two categories: the first category is polymer diluents, which include copolymer polymer viscosity reducers and low molecular weight polymer viscosity reducers. This type of diluent has a low degree of polymerization, and the product often contains a small amount of solvent. The use and recovery of solvents require increased equipment investment and production costs. The other type is dispersed diluents, which include lignin sulfonates, humates, etc. Humic acid is an amorphous polymer hydroxyaromatic carboxylic acid mixture. Because it has a variety of relatively active functional groups and a large surface area, its hydrophilicity, interfacial activity, cation exchange capacity and adsorption and dispersion capacity are all strong. It is a drilling fluid viscosity reducer with promising prospects. Traditional humic acid comes from weathered coal, lignite and peat, and is generally obtained by alkali extraction. However, this type of humic acid has the disadvantages of limited high temperature resistance and general viscosity reduction performance. For example, Apostolidou C and Sards E studied the effectiveness of low-rank lignite as a shear-thinning additive on the rheological behavior and filtration control of drilling fluids after dynamic thermal aging. The results showed that the YP of lignite as a shear-thinning agent after dynamic aging at 177°C tended to or became 0, almost failing, and could not effectively resist the 170°C high-temperature drilling environment. Wenyu Zhang et al. grafted thiophenolic resin onto lignite to synthesize lignite grafted polymers with filtration loss reduction and dispersion properties in water-bentonite slurry. However, while reducing the filtration loss of drilling fluid, the product excessively increased the viscosity of the drilling fluid, causing the problem of excessive viscosity increase of the drilling fluid. In addition, hazardous gases such as SO2 and SO3 will be generated during the experiment, seriously polluting the environment. In general, the defects of the traditional humic acid structure limit the excellent performance of humic acid drilling fluid treatment agents, and it is necessary to find a humic acid raw material with better performance and environmental friendliness.
[0005] Lignin is a natural polymer that mainly exists in plant cell walls. It is one of the most abundant organic compounds in the plant kingdom. Its complex structure and diverse functions make it a research hotspot in many fields. The main sources of lignin include plant cellulose materials such as trees, bamboo, waste paper, and crop straw. These raw materials are widely distributed around the world, providing a rich resource base. At present, lignin is mainly used in the field of bioenergy and can be converted into biofuels such as biodiesel and bioethanol to replace traditional fossil energy and reduce environmental pollution and energy consumption. However, under current technical conditions, the extraction and utilization of traditional lignin have problems such as low utilization rate, high cost, and low added value, which restricts the further development of its large-scale production and application. Faced with these challenges, we urgently need to transform lignin into higher value-added products through innovative technologies and methods to fully release its potential value. Therefore, strengthening the research and development of lignin is of great significance to promoting the development of green industries and building a sustainable social and economic system. Summary of the invention
[0006] The present invention prepares potassium humate (HA-K) by hydrothermal and alkaline extraction of lignin, which has simple process, low cost and high yield. The prepared potassium humate is combined with Na-HPAN, urea, formaldehyde and AAM to synthesize an environmentally friendly potassium humate graft polycondensate Graft HA-K Polymer with novel molecular structure. Then, by simulating the high temperature and high pressure environment of drilling work, its salt resistance and viscosity reduction effects are evaluated. The prepared potassium humate graft polycondensate Graft HA-K Polymer has a temperature resistance of 177.39°C and a resistance to 8000mg·L -1 The high salt point and aging viscosity reduction rate reached 63.16%.
[0007] The present invention provides a method for preparing a potassium humate graft polycondensate Graft HA-K Polymer, comprising the following steps:
[0008] (1) After crushing, grinding and screening, the lignin produced in the biomass processing process is evenly mixed with the modified iron-copper-cerium supported catalyst to maintain a mass ratio of 1:0.5 to 3%;
[0009] (2) uniformly mixing the mixture obtained in (1) and one or more of calcium hydroxide, calcium oxide or calcium chloride so that the mass ratio of lignin to calcium-based raw material is maintained at 1:5 to 40%;
[0010] (3) transferring the mixture obtained in (2) to a hydrothermal kettle, reacting at a temperature range of 150-300° C. for 60-480 min, cooling, and filtering; the filtrate is humic acid liquid fertilizer, and the solid residue is dried in an oven at 80-100° C. to obtain artificial calcium humate;
[0011] (4) impregnating the artificial calcium humate with hydrochloric acid of a certain concentration, filtering, and obtaining a calcium chloride solution and a humic acid precipitate; the calcium chloride solution can be recycled as the calcium-based raw material of step (2);
[0012] (5) dissolving the humic acid precipitate with an alkaline solution of a certain concentration to obtain a potassium humate solution, and drying to obtain a potassium humate solid HA-K;
[0013] (6) Dissolve 1.95 g of potassium humate solid HA-K in 150 mL of water to obtain a potassium humate solution, add hydrolyzed sodium polyacrylonitrile Na-HPAN, urea, formaldehyde, and acrylamide AAM in sequence, react at 60-90° C. for 0.5-3 h, transfer the solution to a reactor, react at 100-300° C. for 1.5-3.5 h, and cool and filter;
[0014] (7) The filtered material is placed in an oven at 80° C. and dried to obtain potassium humate grafted polycondensate GraftHA-K Polymer.
[0015] Furthermore, the sieved lignin and the modified iron-copper-cerium-loaded catalyst in step (1) are uniformly mixed in a mass ratio of 1:1 to 3%, and further uniformly mixed in a mass ratio of 1:3%.
[0016] Furthermore, the preparation process of the modified iron-copper-cerium supported catalyst described in step (1) is as follows: 100 parts by weight of polydimethylsilane are cracked at 400-500°C to obtain liquid polysilane, and then 0.01-0.1 parts of Fe2O3, 0.01-0.1 parts of CuO, 0.01-0.1 parts of Ce(NH4)2(NO3), 0.5-2 parts of azobisisobutyronitrile, 0.5-2 parts of trans-2-dodecenol, and 0.01-0.1 parts of 5-fluoro-8-quinoline acrylic acid are added, and the reaction is carried out for 10-40 hours. The product is dissolved in xylene, filtered, and vacuum distilled to obtain polyiron-copper-cerium carbosilane, which is subjected to porous melt spinning and continuously sintered at 1000-1800°C under the protection of high-purity nitrogen to obtain an iron-copper-cerium supported catalyst.
[0017] Furthermore, the mixture in step (2) is uniformly mixed with one or more of calcium hydroxide, calcium oxide or calcium chloride, and the mass ratio of lignin to calcium-based raw material is 1:10-40%, and further the mass ratio is 1:10-30%.
[0018] Furthermore, in step (3), the mixture obtained in step (2) is transferred to a hydrothermal kettle, the temperature of which is limited to a temperature range of 180-270°C for a time of 120-180 min, and further to a temperature range of 180-250°C for a time of 120-160 min.
[0019] Furthermore, the filtrate in step (3) is humic acid liquid organic water-soluble fertilizer, and the solid residue is placed in an oven at 80° C. and dried to obtain artificial calcium humate.
[0020] Furthermore, the concentration of the hydrochloric acid in step (4) is 10-25%.
[0021] Furthermore, the base in step (5) is KOH or NaOH.
[0022] The present invention also provides a use of the above-mentioned potassium humate graft polycondensate Graft HA-K Polymer as a drilling fluid salt-resistant agent and viscosity reducer.
[0023] The present invention provides a method for preparing a potassium humate graft polycondensate Graft HA-K Polymer, and the principle is as follows:
[0024] Graft HA-K Polymer synthesized by free radical polymerization in solution can reduce the Zeta potential of bentonite particles, thereby reducing the repulsive force of the hydration film, inhibiting the dispersion of clay particles, and destroying the network structure of bentonite. At the same time, in a high temperature environment, the polymer can promote the hydration and dispersion of bentonite, thin the hydration film, weaken the repulsive force between bentonite particles, and make Graft HA-K Polymer have strong salt resistance. The introduction of different groups can increase the hydrolysis of the amide group on the side chain, resulting in the breakage of the macromolecular chain of the copolymer, and the flocculation of bentonite particles into a block structure, reducing the viscosity of the drilling fluid.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] (1) Treating the huge amount of lignin waste generated by the biomass processing industry and realizing the resource utilization of lignin has high economic benefits, strong operability and solves current environmental problems;
[0027] (2) A method for preparing potassium humate by hydrothermal and alkaline extraction of lignin is provided, wherein the yield is high due to the use of a modified iron-copper-cerium supported catalyst;
[0028] (3) Provide a new potassium humate grafted polycondensate Graft HA-KPolymer that is environmentally friendly and has a novel molecular structure. It is synthesized from potassium humate combined with Na-HPAN, urea, formaldehyde, and AAM. It can solve the problems of difficulty in starting pumps, high viscosity, high temperature, and poor resistance of drilling agents to salt invasion in high-temperature and high-pressure salt water formation drilling work, and provide related drilling industry companies with an economical and applicable anti-salt and viscosity-reducing drilling aid, new ideas, and process demonstrations. By simulating the high-temperature and high-pressure environment of drilling work, its anti-salt and viscosity-reducing effects are evaluated. The potassium humate grafted polycondensate Graft HA-KPolymer prepared in this application has a temperature resistance of 177.39°C and a resistance to 8000mg·L -1 The high salt point and aging viscosity reduction rate reached 63.16%. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 , the chemical formula for synthesizing potassium humate graft polycondensate Graft HA-K Polymer;
[0030] Figure 2 , the effect of sodium chloride on (a) AV, (b) PV, (c) YP, and (d) FL values (after adding 3.0 wt% of Graft HA-K Polymer and aging at 120 °C for 16 h);
[0031] Figure 3, the technical roadmap for the preparation of drilling fluid anti-salt viscosity reducer by utilizing lignin resources;
[0032] Figure 4 , (a) C-HA-K (b) HA-K (c) Graft C-HA-K Polymer (d) SEM image of Graft HA-K Polymer
[0033] Figure 5 、(a)WBDF;(b)WBDF+NaCl;
[0034] (c)WBDF+Graft C-HA-Kpolymer;
[0035] (d)WBDF+NaCl+Graft C-HA-Kpolymer;
[0036] (e) WBDF+Graft HA-K Polymer;
[0037] (f) SEM image of WBDF+NaCl+Graft HA-K Polymer after aging at 120℃ for 16h DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0039] The technical solution of the present invention is further explained below in conjunction with implementation cases.
[0040] C-HA-K was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0041] The preparation method of the modified iron-copper-cerium supported catalyst is as follows:
[0042] By weight, 100 parts of polydimethylsilane are cracked at 400-500°C to obtain liquid polysilane, and then 0.01-0.1 parts of Fe2O3, 0.01-0.1 parts of CuO, 0.01-0.1 parts of Ce(NH4)2(NO3), 0.5-2 parts of azobisisobutyronitrile, 0.5-2 parts of trans-2-dodecenol, and 0.01-0.1 parts of 5-fluoro-8-quinoline acrylic acid are added, and the reaction is carried out for 10-40 hours. The product is dissolved in xylene, filtered, and vacuum distilled to obtain polyiron-copper-cerium carbosilane, which is subjected to porous melt spinning and continuously sintered at 1000-1800°C under the protection of high-purity nitrogen to obtain an iron-copper-cerium supported catalyst.
[0043] Example 1
[0044] This embodiment provides a method for preparing lignin potassium humate HA-K, and the specific steps are as follows:
[0045] (1) After lignin is crushed, ground and sieved, 100 g of lignin powder and 1 g of iron, copper and cerium supported catalyst are mixed evenly;
[0046] (2) uniformly mixing the mixture obtained in (1) and 30 g of calcium chloride;
[0047] (3) The mixture obtained in (2) is transferred to a hydrothermal kettle, reacted at 180°C for 120 minutes, cooled, and filtered. The filtrate is humic acid liquid fertilizer, and the solid residue is dried in an oven at 80°C to obtain artificial humic acid calcium;
[0048] (4) The artificial calcium humate obtained in (3) is adjusted to a pH of 1-2 with dilute hydrochloric acid, filtered, and a calcium chloride solution and humic acid precipitate are obtained. The calcium chloride solution is recycled as the calcium-based raw material and catalyst in step (2).
[0049] (5) The precipitate obtained in (4) was dissolved in 30% KOH, and the filtrates obtained under different conditions were placed in an oven at 80°C to dry to obtain HA-K. The yield of HA-K under different conditions was calculated.
[0050] The yield of HA-K was calculated using formula (1):
[0051]
[0052] In the formula: y-Yield ofHA-K,%;
[0053] m-Mass of humic acid Potassium obtained,g;
[0054] m1-Mass of Lignin, g.
[0055] Comparative Example 1
[0056] Fe2O3 is not added, and the rest is the same as in Example 1.
[0057] Comparative Example 2
[0058] CuO was not added, and the rest was the same as in Example 1.
[0059] Comparative Example 3
[0060] Ce(NH4)2(NO3) was not added, and the rest was the same as in Example 1.
[0061] Comparative Example 4
[0062] Trans-2-dodecenol was not added, and the rest was the same as in Example 1.
[0063] Comparative Example 5
[0064] 5-Fluoro-8-quinoline acrylic acid was not added, and the rest was the same as in Example 1.
[0065] Table 1: Yield of HA-K made by different processes (%)
[0066] serial number Yield % Example 1 75% Comparative Example 1 66% Comparative Example 2 62% Comparative Example 3 60% Comparative Example 4 45% Comparative Example 5 34%
[0067] Example 2
[0068] This embodiment provides a method for preparing a potassium humate graft polycondensate Graft HA-K Polymer, and the specific steps are as follows:
[0069] (1) 100 g of potassium humate solid prepared in Example 1 was dissolved to obtain a potassium humate solution, and different amounts of Na-HPAN, urea, formaldehyde, and AAM were added in sequence. After reacting at 70° C. for 0.5 h, the solution was transferred to a reactor, reacted at 150° C. for 3.0 h, and then cooled and filtered;
[0070] (2) The filtered material is placed in an oven at 80° C. and dried to obtain potassium humate grafted polycondensate GraftHA-K Polymer.
[0071] The chemical formula of potassium humate graft polycondensate Graft HA-K Polymer can be found in Figure 1 .
[0072] Potassium humate grafted polycondensate GraftHA-K Polymer was prepared using different contents of Na-HPAN, urea, formaldehyde and AAM.
[0073] Table 2 Orthogonal experimental table of potassium humate graft polycondensation product Graft HA-K Polymer
[0074]
[0075] Note: Potassium humate grafted polycondensate comparative example 1, referred to as polycondensate 1;
[0076] Potassium humate grafted polycondensate comparative example 2, referred to as polycondensate 2;
[0077] Potassium humate grafted polycondensate comparative example 3, referred to as polycondensate 3.
[0078] Example 3
[0079] This embodiment provides a method for preparing a potassium humate graft polycondensate Graft C-HA-K Polymer, the specific steps of which are:
[0080] (1) 1.95 g C-HA-K (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) was dissolved in 150 ml water to obtain a potassium humate solution, and 10 g Na-HPAN, 16 g urea, 20 ml formaldehyde, and 2 g AAM were added in sequence. After reacting at 70° C. for 0.5 h, the solution was transferred to a reactor, reacted at 150° C. for 3.0 h, and then cooled and filtered;
[0081] (2) The filtered material is placed in an oven at 80°C and dried to obtain potassium humate grafted polycondensate Graft C-HA-K Polymer.
[0082] Graft HA-K Polymer Viscosity Reduction Performance Test
[0083] Sodium bentonite was purchased from Hami Shentu Technology Co., Ltd.
[0084] The water-based drilling fluid was prepared by dissolving 20 g of sodium bentonite in 500 mL of deionized water and stirring at high speed for 20 minutes.
[0085] Table 3 lists the viscosity reduction ability and rheological properties of water-based drilling fluids with different viscosity reducers of 3.0 wt% bentonite before and after the thermal aging test. By comparing the viscosity reduction results of different experimental groups before and after thermal aging, it is found that before aging, the viscosity reduction rate of modified experiment 1 is the highest, up to 58.62%, and the effect is the most obvious; after aging, the viscosity reduction rate of modified experiment 1 is the highest, up to 63.16%, and the effect is the most obvious.
[0086] Table 3 Rheological parameters of various fluid formulations
[0087]
[0088] Note:
[0089] Base fluid is water-based drilling fluid;
[0090] C-HA-K fluid is a water-based drilling fluid to which commercially available C-HA-K material is added;
[0091] HA-K fluid is a water-based drilling fluid to which HA-K prepared in Example 1 is added;
[0092] Temperature resistance test of Graft HA-K Polymer
[0093] Sodium bentonite was purchased from Hami Shentu Technology Co., Ltd.
[0094] The water-based drilling fluid was prepared by dissolving 20 g of sodium bentonite in 500 mL of deionized water and stirring at high speed for 20 minutes.
[0095] Table 4 shows the rheological parameters of the fluid formula (water-based drilling fluid with 3.0 wt% of bentonite mass of Graft HA-K Polymer) at different aging temperatures. 3.0 wt% of Graft HA-K Polymer was added to the 4% fresh water-based slurry after curing for 24 hours, and after high-speed stirring at 10000 rpm for 20 minutes, it was aged for 16 hours at different aging temperatures (80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180°C). By measuring the rheological parameters and filtration loss before and after aging of the drilling fluid, it was determined that the viscosity reducer has a temperature resistance of 177.39°C.
[0096] Table 4 Effect of temperature on rheological properties of condensation polymer fluids with 3.0 wt% addition
[0097]
[0098]
[0099] Salt resistance test of Graft HA-K Polymer
[0100] During oil drilling, insufficient salt corrosion resistance of the treating agent may lead to hole wall collapse. Figure 2 The rheological parameters of different fluid formulations under different NaCl concentrations are shown. Different proportions of NaCl (0, 1, 2.5, 5, 10, 20%) were added to the freshwater base slurry after curing for 24 hours. After curing for 24 hours, 3.0wt% of Graft HA-K Polymer was added. After high-speed stirring at 10000rpm for 20 minutes, it was aged at the optimal aging temperature for 16 hours. By measuring the rheological parameters and filtration loss before and after aging of the drilling fluid, it was determined that the viscosity reducer has the ability to withstand 8000mg·L -1 high salt point.
[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a potassium humate graft polycondensate Graft HA-K Polymer, characterized in that: The steps include: (1) After crushing, grinding and screening, the lignin produced in the biomass processing process is evenly mixed with the modified iron-copper-cerium supported catalyst to maintain a mass ratio of 1:0.5 to 3%; (2) uniformly mixing the mixture obtained in (1) and one or more of calcium hydroxide, calcium oxide or calcium chloride so that the mass ratio of lignin to calcium-based raw material is maintained at 1:5 to 40%; (3) transferring the mixture obtained in (2) to a hydrothermal kettle, reacting at a temperature range of 150-300° C. for 60-480 min, cooling, and filtering; the filtrate is humic acid liquid fertilizer, and the solid residue is dried in an oven at 80-100° C. to obtain artificial calcium humate; (4) impregnating the artificial calcium humate with hydrochloric acid of a certain concentration, filtering, and obtaining a calcium chloride solution and a humic acid precipitate; the calcium chloride solution can be recycled as the calcium-based raw material of step (2); (5) dissolving the humic acid precipitate with an alkaline solution of a certain concentration to obtain a potassium humate solution, and drying to obtain a potassium humate solid HA-K; (6) Dissolve 1.95 g of potassium humate solid HA-K in 150 mL of water to obtain a potassium humate solution, add hydrolyzed sodium polyacrylonitrile Na-HPAN, urea, formaldehyde, and acrylamide AAM in sequence, react at 60-90° C. for 0.5-3 h, transfer the solution to a reactor, react at 100-300° C. for 1.5-3.5 h, and cool and filter; (7) The filtered material is placed in an oven at 80°C and dried to obtain potassium humate grafted polycondensate Graft HA-KPolymer.
2. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: In step (1), the sieved lignin and the modified iron-copper-cerium supported catalyst are uniformly mixed in a mass ratio of 1:1 to 3%.
3. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: The preparation process of the modified iron-copper-cerium supported catalyst described in step (1) is as follows: 100 parts by weight of polydimethylsilane are cracked at 400-500° C. to obtain liquid polysilane, and then 0.01-0.1 parts of Fe2O3, 0.01-0.1 parts of CuO, 0.01-0.1 parts of Ce(NH4)2(NO3), 0.5-2 parts of azobisisobutyronitrile, 0.5-2 parts of trans-2-dodecenol, and 0.01-0.1 parts of 5-fluoro-8-quinoline acrylic acid are added, and the reaction is carried out for 10-40 hours. The product is dissolved in xylene, filtered, and vacuum distilled to obtain polyiron-copper-cerium carbosilane, which is subjected to porous melt spinning and continuously sintered at 1000-1800° C. under the protection of high-purity nitrogen to obtain an iron-copper-cerium supported catalyst.
4. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: The mixture in step (2) is uniformly mixed with one or more of calcium hydroxide, calcium oxide or calcium chloride, and the mass ratio of lignin to calcium-based raw material is 1:10-30%.
5. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: Step (3) transfers the mixture obtained in step (2) into a hydrothermal kettle, wherein the temperature is limited to the range of 180-270° C. and the time is 120-180 min.
6. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: The filtrate in step (3) is humic acid liquid organic water-soluble fertilizer, and the solid residue is placed in an oven at 80° C. and dried to obtain artificial calcium humate.
7. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: The concentration of the hydrochloric acid in step (4) is 10-25%.
8. The method for preparing the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1, characterized in that: The base described in step (5) is KOH or NaOH.
9. Use of the potassium humate graft polycondensate Graft HA-K Polymer according to claim 1 as a drilling fluid anti-salt agent and viscosity reducer.
